Molecular Response of Dodonaea Viscosa Chloroplast Genes to Environmental Stress Factors - Omer, Mohammed Khatab (American Journal of Biology and Natural Sciences, 2026)
Dodonaea viscosa plant is characterized by a highly stress-tolerant and provides an important plant for studying chloroplast gene responses to environmental stresses. The aim of this study was to discuss the differential expression of plastid genes (clpP, ccsA, rpoC1, and ycf1) at various sites in Salahaddin Governorate, Iraq, which characterized by different levels of pollution from vehicle traffic, wastewater and industrial activities. Using (qRT-PCR) a significant increase in the gene expression levels of all four genes was observed in plants taken from site near the Baiji oil refinery, indicating robust transcriptional reprogramming in response to chemical-oxidative stress. The increased of the clpP gene expression show activation of the proteolytic system in chloroplasts to mitigate protein damage, while the increased expression of the ccsA gene indicated adaptive enhancement of the system of electron transport. The increased expression of the rpoC1 gene reflected a stress-induced modification of chloroplast encoded RNA polymerase, while the expression of the ycf1 gene was associated with pollutant-induced oxidative stress and chloroplast membrane regulation. while the samples from unpolluted sites showed expression levels close to basal and intermediate responses were observed in sites affected by wastewater. The increased expression of the rpoC1 gene reflected a stress-induced modification of chloroplast encoded RNA polymerase, while the expression of the ycf1 gene was associated with pollutant-induced oxidative stress and chloroplast membrane regulation. while the samples from unpolluted sites showed expression levels close to basal and intermediate responses were observed in sites affected by wastewater. These results demonstrate that these genes in D. viscosa function as molecular marker sensitive to environmental changes and pollution. Furthermore, the results underscore the significant potential of this species as a bioindicator plant for monitoring environmental degradation and suggest that chloroplast gene expression can provide early warnings of ecosystem-level impacts. Future studies recommend expanding the gene pool and integrating environmental data to develop more robust bioindicator systems for plant-based environmental monitoring.